Normally we charge $1.00 for this answer

Today, you can get it FOR FREE if you

g+1, Follow or Like, us

Show me how to post my homework

Just do my homework!

  • HTML tags will be transformed to conform to HTML standards.
  • Add rel="nofollow" to external links
Question
Submitted by kryzskosr on Thu, 2012-03-01 11:46
due date not specified
answered 2 time(s)
kryzskosr bought 0 out of 1 answered question(s)
one anonymous student showed interest

4x-5=-3

4x-5=-3

Answer
Submitted by Andrein on Thu, 2012-03-01 15:41
teacher rated 2 times
3
price: $1.00

x=0.5 (Complete answer below)

body preview (62 words)

4 x x x x = x x

xxxxx xx add x xx xxxx xxxxx and we have:

4 x x - 5 x 5 = - 3 + x =>

4 * x + 0 x 2 x>

4 * x = x

xxx xx xxxxxx both xxxxx by x and we xxxxx

x * x /4 x 2/4 x>

x x 4/4 = xxx =>

x x 1 = xxx =>

x x xxx x>

x x xxx x xxx

x

.

xx xxx xxxx further xxxxxxxxx regarding xx xxxxxxxx please send xx a xxxxxxx and I xxxx reply xx xxxx xx xxxxxxxxx

Have a nice xxxx


Buy this answer

Answer
Submitted by dayamath on Thu, 2012-03-01 11:58
teacher rated 0 times
0
price: $1.00

complete answer:

body preview (33 words)

4x-5=-3 xx xxx 5 to both xxxxx xx this equation xx obtain xxxx +5 x xx xx

xxxx xx = 2 we divide both xxxxx xx xxxx last equation xx 4 xxxx 4x/4 = xxx

xxxx x x 2/4 x xxx

then xxx xxxxxxxx is 1/2


Buy this answer